2017
DOI: 10.1055/s-0043-117610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drop-height and Surface Instability on Jump Performance and Knee Kinematics

Abstract: The purpose of this study was to examine the combined effects of drop-height and surface condition on drop jump (DJ) performance and knee joint kinematics. DJ performance, sagittal and frontal plane knee joint kinematics were measured in jump experienced young male and female adults during DJs on stable, unstable and highly unstable surfaces using different drop-heights (20, 40, 60 cm). Findings revealed impaired DJ performance (Δ5-16%; p<0.05; 1.43≤d≤2.82), reduced knee valgus motion (Δ33-52%; p<0.001; 2.70≤d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Therefore, 100 %CMJH may be the turning point for any observed biomechanical changes in the relative drop heights for DJ plyometric training intensity. These findings were similar to previous investigations from absolute drop heights that reported both rapid and powerful DJ performance increased from 35- [37] and 40-cm [38,39] and reported those as the turning point compared to greater heights. Larger drop heights may lead to decrements of DJ performances due to a reduction from the SSC, which might be a protective strategy for preventing muscle and tendon injury associated with a higher impact GRF [8,9,19].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, 100 %CMJH may be the turning point for any observed biomechanical changes in the relative drop heights for DJ plyometric training intensity. These findings were similar to previous investigations from absolute drop heights that reported both rapid and powerful DJ performance increased from 35- [37] and 40-cm [38,39] and reported those as the turning point compared to greater heights. Larger drop heights may lead to decrements of DJ performances due to a reduction from the SSC, which might be a protective strategy for preventing muscle and tendon injury associated with a higher impact GRF [8,9,19].…”
Section: Discussionsupporting
confidence: 91%
“…The DJ performance remained unchanged with incremental drop heights in the current study, which agreed with Bassa et al [40] and Bencke et al [41] but contrasted with Prieske et al [37], Andrade et al [38] and Lesinski et al [39]. Prieske et al [37] reported that both the DJH and RSI increased with drop heights from 20-to 50-cm and from 20-to 35-cm, respectively, in 239 adolescent handball players, irrespective of sex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, training surface (i.e., soft versus hard surfaces) has to be taken into account and might affect training-related outcomes as well. Studies with adults have shown that plyometric exercises performed under unstable conditions can result in performance decrements [ 135 ] and altered kinematic responses (joint range of movement) compared to plyometrics under stable conditions [ 136 , 137 ]. Research comparing plyometrics on stable versus unstable surface in children and adolescents showed mixed results [ 85 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within conditions were the SGS is known, variation in SGS is associated with changes in peak force [11], jump height [10,11], ground contact time [10,11] and joint kinematics [11,12,17,18]. Concomitantly, adaptations in muscle pre-activation prior to ground contact [11,12,19] and subsequent concentric phase have been reported [11,13].…”
Section: Introductionmentioning
confidence: 99%